PENGARUH TAX PLANNING, TAX AVOIDANCE DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN: NILAI PERUSAHAAN - Santika Betara; Titah Rahmawati (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This study aims to examine the influence of Tax Planning, Tax Avoidance, and Good Corporate Governance (GCG) on company value in the financial institutions sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Company value is measured using the  to Book Value (PBV) ratio. Tax Planning is proxied by the Effective Tax Rate (ETR), Tax Avoidance by the Cash Effective Tax Rate (CETR), and GCG is measured through institutional ownership. This study uses a quantitative method with secondary data obtained from annual financial reports. The study population includes 32 financial institutions. The sample was determined using a purposive sampling method, resulting in 18 companies over five years of observation. The analysis technique used is panel data regression, with the best model based on the Chow and Hausman test being the Fixed Effect Model (FEM). The results show that Tax Planning and Good Corporate Governance have no significant effect on company value, while Tax Avoidance has a significant effect on company value. These findings indicate that tax avoidance, despite its potential risks, can be positively perceived by the market if conducted within legal limits, while tax planning and institutional ownership are not necessarily the primary factors in increasing company value in this sector. Keywords: Company Value, Financing Institutions, Good Corporate Governance, Tax Avoidance, Tax                                   Planning.